2022
DOI: 10.1039/d2tc00545j
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the anion stoichiometry and oxidation kinetics of vanadium (oxy)nitride by the control of ammonolysis conditions

Abstract: Higher N/O increases significantly the V(O,N) oxidation resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…7 shows the SEM micrographs of the Nb 2 O 5 precursor as well as niobium oxynitride powders synthesized for 12 h as a function of temperature. From the SEM results, no significant morphological differences were observed, in good agreement with previous literature, 54 in which authors reported that the use of ammonolysis does not substantially influence the final morphology of the obtained powders.…”
Section: Structural Characterizationsupporting
confidence: 91%
See 3 more Smart Citations
“…7 shows the SEM micrographs of the Nb 2 O 5 precursor as well as niobium oxynitride powders synthesized for 12 h as a function of temperature. From the SEM results, no significant morphological differences were observed, in good agreement with previous literature, 54 in which authors reported that the use of ammonolysis does not substantially influence the final morphology of the obtained powders.…”
Section: Structural Characterizationsupporting
confidence: 91%
“…The cation-vacancy mechanism of (eqn 7) cannot fulfill this requirement, as this equation infers a constant cation oxidation state of 3 + , with ammonolysis, as recently experimentally shown for vanadium oxynitrides. 28 An equivalent case to vanadium oxynitride is not seen in the current work, and, thus, cation vacancies alone cannot explain the measured stoichiometries of the present niobium oxynitride system.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…Figures – show the XPS results of the surface composition variation of the TiZrV NEG films after undergoing different storage periods when wrapped by aluminum foil. With prolonging the storage time under conditions set in this research, a significant change of the film surface layer has occurred: For the N 1s spectra, there were some amounts of N–H and AlN* were gradually formed apart from the moderate-screened γ-N 2 , well-screened γ-N 2 , and M-N For the C 1s spectra, C x H y has undergone more significant changes in terms of structure and content compared to other carbonaceous compositions such as −COO–, −CO–, ,, and carbides. , For the O 1s spectra, the content of oxides decreased greatly as C x H y increased significantly. For different metallic elemental p or d spectra, various kinds of oxides (TiO 2 , Ti 2 O 3 , ZrO 2 , and VO 2 ), hydroxyl groups (Ti-hydroxyl groups, Zr-hydroxyl groups, and V-hydroxyl groups), and carbides (TiC, ZrC*, and VC) were detected on the surface or in the surface layer of the film. …”
Section: Resultsmentioning
confidence: 92%